Knowledge and Management Practices Against Malaria in Isulo Community, Orumba South L.G.A Anambra State, Nigeria - A. E., Onyido; C. A., Ughaelu; K.C. , Irikannu; P. U. , Umeanaeto; M.O. , Iwueze; A. C. , Ezeani; E. N., Okafor (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
A study to determine the knowledge of, and management practices against malaria among thepeople of Isulo community in Orumba South Local Government Area of Anambra State, Nigeria, wascarried out between April and June 2014. Structured questionnaires were issued to 500 individuals in thecommunity. Personal data including age, sex, educational status, marital status and occupation werecollected with the questionnaire. Educational attainment of the participants were Primary education100(20.0%), Secondary education 60(12.0%), tertiary education 45(9.0%), and non-formal education250(50.0%). All the respondents, 500(100%), were aware of the malaria disease. All the respondents,500(100%) mentioned body weakness, headache and fever as the common symptoms of alaria.480(96.0%) respondents attributed malaria to mosquito bites, 290(58.0%) attributed it to consumption oftoo much of oil, 320(64.0%) attributed it to drinking dirty water. On protective measures against mosquitobites, 500(100%) reported putting of nets on the windows and doors and 485(97.0%) believed on sprayinginsecticide inside houses and sleeping under insecticide-treated nets could prevent mosquito bites. Most ofthe respondents 490(98.0%) believed that malaria needs to be treated while 10(2.0%) said that it was adisease that heals on its own without treatment. Malaria treatment methods of the people included visit tohealth centres or hospital 410(82.0%), buying drugs from chemist shops 195(39.5%), visiting prayer andhealing homes 170(34.0%), use of herbs 415(83.0%), avoidance of oily foods 325(69.0%), self-medication165(33.0%) and no treatment 30(6.0%). There is need to empower them with information about the causesof malaria and proper management practices.